2020
DOI: 10.1186/s12879-020-05462-0
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective analysis of the etiology, clinical characteristics and outcomes of community-acquired bacterial meningitis in the University Infectious Diseases Centre in Lithuania

Abstract: Background The morbidity and mortality in community-acquired bacterial meningitis (CABM) remain substantial, and the etiology, clinical characteristics, treatment outcomes and predictors of poor prognosis must be assessed regularly. The aim of this study was to identify the distribution of etiological agents and their relationship with clinical characteristics, treatment and outcomes in this cohort of patients with CABM. Methods Our retrospective chart review analyzed the causative microorganisms, clinical c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 35 publications
4
11
1
Order By: Relevance
“…Therefore, it is clear that the absence of the classical triad cannot be used to rule out the possibility of BM. In an older study headache was not reported to be correlated with unfavorable outcome [ 26 ], but with a more recent study [ 37 ] headache was correlated with unfavorable outcome, as was the case also in our study. Therefore, clinicians should pay even more attention to BM patients suffering from headache and not only altered mental status, which may be a sign of a more advanced disease.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Therefore, it is clear that the absence of the classical triad cannot be used to rule out the possibility of BM. In an older study headache was not reported to be correlated with unfavorable outcome [ 26 ], but with a more recent study [ 37 ] headache was correlated with unfavorable outcome, as was the case also in our study. Therefore, clinicians should pay even more attention to BM patients suffering from headache and not only altered mental status, which may be a sign of a more advanced disease.…”
Section: Discussionsupporting
confidence: 81%
“…Triad of fever, neck stiffness and altered mental status has been previously reported with 41–59% BM cases [ 37 , 38 ]. In our study, the prevalence of the presentation with this triad was much lower (13.5%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this country, the most common serotype responsible for the disease was B, infecting mainly young children. However, vaccination against meningitidis B has only been routinely introduced in Lithuania since 2018 [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Second, neu ro log i cal con di tion on ad mis sion is not the only fac tor de ter min ing the clin i cal course of acute bac te rial men in gi tis. Fac tors of poor out come in clude older age [5,[23][24][25][26][28][29][30], more spe cif i cally, age ³40 years [24], age >50 years [5], age ³60 years [28], age >65 years [29], age >70 years [26]; comorbidities [16,23,26,28,29]; re duced platelet count [24,29,31]; worse over all clin i cal con di tion as de fined by Sim pli fied Acute Phys i ol ogy Score (SAPS) II [31] or APACHE II [5]; low CSF glu cose lev els [28,32]; low CSF leu ko cyte count [25,26,33]; tachy car dia [33], as well as fac tors show ing se ver ity of dis ease (ev i dence of shock, sep sis, and bacteraemia) [2,24,26,28]. To em phasize the im por tance of other fac tors in ad di tion to neu rolog i cal con di tion to in flu ence the out come of pa tients with bac te rial men in gi tis, Weisfelt et al, 2008 [33] are worth not ing.…”
Section: Discussionmentioning
confidence: 99%